2005
DOI: 10.1161/01.res.0000158964.42008.a2
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Protein–Specific Regulation of Cx43 Expression in Cardiac Myocytes Subjected to Mechanical Load

Abstract: Abstract-To elucidate mechanisms responsible for mechanotransduction in the heart and define the effects of remodeling of the extracellular matrix, we cultured neonatal rat ventricular myocytes on native type I collagen, fibronectin, or denatured collagen and subjected them to uniaxial, pulsatile stretch. Changes in expression of the cardiac gap junction protein, Cx43, were measured by confocal microscopy and immunoblotting. Cells grown on fibronectin or denatured collagen exhibited significantly greater Cx43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…The reliability of the GJIC assay is supported by a comparison of dye diffusion between the risk and non-risk areas in the same section after coronary occlusion. Several studies have demonstrated causality between Cx43 upregulation and GJIC activation, [11][12][13] and the phosphorylated state of Cx43 also mediates Cx43 distribution to GJs and regulation of GJIC activity. Phosphorylation at serine residues 325, 328 and/or 330 (pS325/328/330-Cx43) promotes distribution of Cx43 to GJs and enhances GJIC, 14 and phosphorylation at serine 365 (pS365-Cx43) has a "gatekeeper" function.…”
Section: Causality Of Cx43 Translocation With Gjic Enhancementmentioning
confidence: 99%
“…The reliability of the GJIC assay is supported by a comparison of dye diffusion between the risk and non-risk areas in the same section after coronary occlusion. Several studies have demonstrated causality between Cx43 upregulation and GJIC activation, [11][12][13] and the phosphorylated state of Cx43 also mediates Cx43 distribution to GJs and regulation of GJIC activity. Phosphorylation at serine residues 325, 328 and/or 330 (pS325/328/330-Cx43) promotes distribution of Cx43 to GJs and enhances GJIC, 14 and phosphorylation at serine 365 (pS365-Cx43) has a "gatekeeper" function.…”
Section: Causality Of Cx43 Translocation With Gjic Enhancementmentioning
confidence: 99%
“…Previous studies of other cell types have reported an upregulation of gap junction communication with altered integrin-matrix interactions (Czyz et al, 2005;Lampe et al, 1998;Shanker et al, 2005). CNCs were impaled with microelectrodes and the gap junction permeable fluorescent tracer, carboxyfluorescein, was iontophoretically injected (Fig.…”
Section: Gap Junction Communication Unchanged With Different Fibronecmentioning
confidence: 99%
“…␤ 1 -Integrin is abundantly expressed in type II cells and seems essential for the development of the lung epithelium (2), for cell anchoring to different substrates (9), and as mechanoreceptor in many other cell types (20,29,37,44,48,51,53). In agreement with these studies, cell adhesion experiments demonstrated that ␤ 1 -integrin mediates type II cell attachment to laminin substrates.…”
Section: Discussionmentioning
confidence: 67%